Authenticity and innovation in the development of cultural tourism villages in Tanah Datar regency / Sarojini Imran and Nungki Puspita - Imran, Sarojini; Puspita, Nungki (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The research aims to provide a comprehensive understanding of how authenticity and innovation contribute to cultural tourism villages in Tanah Datar Regency. By analyzing the authenticity and innovation of cultural products in the development of cultural tourism destination areas in Tanah Datar Regency, it also aims to examine institutional collaboration and community participation in the development of tourism villages in Tanah Datar Regency. The methodology outlines a qualitative analysis approach, including case studies, participatory observation, content analysis, and theme analysis. Data triangulation is employed for reliability. The results of this study indicate that authentic cultural products in Tanah Datar are well-preserved by the community, with a traditional institutional system involving the younger generation in innovative packaging of these authentic products. The role of the Tanah Datar government is considered supportive of the preservation of cultural authenticity through the innovative policy of designing a calendar of events called "One Nagari, One Event." This policy has successfully mobilized community involvement in organizing events in their villages, simultaneously promoting their cultural richness to a broader audience, not only within Tanah Datar Regency but also nationally and even internationally.